Mixed Ammonium-Nitrate Nutrition Regulates Enzymes, Gene Expression, and Metabolic Pathways to Improve Nitrogen Uptake, Partitioning, and Utilization Efficiency in Rice - Xianting Fan; Chusheng Lu; Zaid Khan; Zhiming Li; Songpo Duan; Hong Shen; Youqiang Fu (Plants)
Ammonium and nitrate nitrogen are the two main forms of inorganic nitrogen (N) available to crops. However, it is not clear how mixtures of ammonium and nitrate N affect N uptake and partitioning in major rice cultivars in southern China. This study investigated the effects of different ammonium nitrogen and nitrate nitrogen mixture treatments (100:0, 75:25, 50:50, 25:75, and 0:100) on the growth, photosynthetic characteristics, nitrogen uptake, gene expression, and yield of different rice cultivars (Mei Xiang Zhan NO. 2: MXZ2; Nan Jing Xiang Zhan: NJXZ). Rice root biomass, tiller number, and yield were increased by 69.5%, 42.5%, and 46.8%, respectively, in the 75:25 ammonium-nitrate mixed treatment compared to the 100:0 ammonium-nitrate mixed treatment. The nitrogen content in rice roots, stems, leaves, and grains increased by 69.5%, 64.0%, 65.5%, and 17.5%, respectively. In addition, compared with MXZ2, NJXZ had a greater proportion of N allocated to leaves and grains. Analysis of root enzyme activities revealed that the 75:25 ammonium-nitrate mixed nutrient treatment increased rice root glutamine synthetase activity by an average of 35.0% and glutamate synthetase activity by an average of 52.0%. Transcriptome analysis revealed that the 75:25 mixed ammonium-nitrate nutrient treatment upregulated the expression of genes related to the nitrogen metabolism transporter pathway. Weighted correlation network analysis revealed that some differentially expressed genes (HISX and RPAB5) regulated the activities of nitrogen-metabolizing enzymes in rice and some (SAT2, CYSKP, SYIM, CHI1, and XIP1) modulated amino acid synthesis; greater expression of these genes was detected in the 75:25 ammonium-nitrate mixed nutrient treatment. The expression characteristics of the above genes were further confirmed by RT‒qPCR. Interestingly, the expression levels of the above genes were significantly correlated with the glutamate synthase activity, photosynthetic rate, and root volume. It is noteworthy that increasing the expression of the aforementioned genes coupled with nitrogen uptake was observed in the three main rice cultivars. These results suggest that the 75:25 ammonium-nitrate mixture may have increased nitrogen-metabolizing enzyme activities and promoted nitrogen uptake through the upregulated expression of nitrogen metabolism-related genes, thereby increasing tiller number and improving rice yield.